Philosophy and Blade Runner - Shanahan, Timothy. author. aut Link
XIII, 217 p.
Keywords: Philosophy and Blade Runner explores philosophical issues in the film Blade Runner , including human nature, personhood, identity, consciousness, free will, morality, God, death, and the meaning of life. The result is a novel analysis of the greatest science fiction film of all time and a unique contribution to the philosophy of film.